The Complexity of Blood Pressure Fluctuation Mediated the Effects of Hypertension on Walking Speed in Older Adults - Jiang, Xin; Cai, Yurun; Zhao, Yue; Gao, Xia; Peng, Dan; Zhang, Hui; Deng, Wuhong; Fu, Wen; Qin, Na; Chang, Ruizhen; Manor, Brad; Zhou, Junhong (Frontiers in Aging Neuroscience, 2021)
Background: Older adults with hypertension often had diminished walking performance. The underlying mechanism through which hypertension affects walking performance, however, has not been fully understood. We here measured the complexity of the continuous systolic (SBP) and diastolic (DBP) blood pressure fluctuation, grade of white matter lesions (WMLs), and cognitive function and used structural equation modeling (SEM) to examine the interrelationships between hypertension, BP complexity, WMLs, cognitive function, and walking speed in single- and dual-task conditions. Methods: A total of 152 older adults with age > 60 years (90 hypertensive and 62 normotensive participants) completed one MRI scan of brain structure, a finger BP assessment of at least 10 min, Mini-Mental State Examination (MMSE) to assess cognitive function, and 10-meter walking tests in single (i.e., normal walking) and dual tasks (i.e., walking while performing a serial subtraction of three from a random three-digit number). The grade of WMLs was assessed using the total score of Fazekas scale; the complexity of SBP and DBP was measured using multiscale entropy (MSE), and the walking performance was assessed by walking speed in single- and dual-task conditions. Results: As compared to normotensives, hypertensive older adults had significantly slower walking speed, lower complexity of SBP and DBP, greater grade of WMLs, and poorer cognitive function (p < 0.03). Those with lower BP complexity (β > 0.31, p < 0.003), greater WML grade (β < −0.39, p < 0.0002), and/or poorer cognitive function (β < −0.39, p < 0.0001) had slower walking speed in single- and/or dual-task conditions. The SEM model demonstrated significant total effects of hypertension on walking speed, and such effects were mediated by BP complexity only, or BP complexity, WML grade, and cognitive function together. Conclusion: This study demonstrates the cross-sectional association between the complexity of continuous beat-to-beat BP fluctuation, WML grade, cognitive function, and walking speed in hypertensive and normotensive older adults, revealing a potential mechanism that hypertension may affect walking performance in older adults through diminished BP complexity, increased WML grade, and decreased cognitive function, and BP complexity is an important factor for such effects. Future longitudinal studies are warranted to confirm the findings in this study.